ANALISIS DIMENSI KUALITAS PELAYANAN IMPLIKASINYA TERHADAP KEPUASAN NASABAH PADA LEMBAGA PERKREDITAN DESA (LPD) DESA ADAT BONGLI PENEBEL – TABANAN - Ni Ketut Karwini; Ni Wayan Ana Rahita Handayani (Universitas Triatma Mulya, 2021)
Business competition is very tight at this time, both making every company really have to meet customer satisfaction, including financial service companies, including banking, LPD, and others. Quality service quality can create customer satisfaction. Companies that are able to compete in the market are companies that can provide quality products or services, so that companies are required to continue to improve the quality of their services. The purpose of this study was to determine and analyze the effect simultaneously and partially on the dimensions of service quality consisting of Tangibles, Reliability, Responsiveness, Assurance and Empathy on customer satisfaction at the Village Credit Institution (LPD), Bongli Traditional Village, Penebel in Tabanan. The type of data used is quantitative and qualitative data with primary data and secondary data. The data collection methods used in this study were questionnaires and document study, while the data analysis technique used in this study was the classical assumption test which included normality test, multicolineartity test, autocorrelation test, heteroscedasticity test, and multiple regression analysis, multiple correlation analysis. , simultaneous regression coefficient test (F-test), partial regression coefficient test (t-test) and analysis of determination. The results showed that there was simultaneously a significant influence between service quality and customer satisfaction; it is partially known that there are 5 (five) dimensions that affect customer satisfaction; The results of the determination analysis obtained R2 = 0.489 (48.90%) means that 48.90% of customer satisfaction is influenced by service quality, while the remaining 51.10% is influenced by other factors not included in this study; Furthermore, it can be seen from the beta coefficient that it can be seen that the responsiveness dimension is the most dominant in influencing customer satisfaction with the largest coefficient value of 0.320 (32%).